Arbitraż w posttotalitarnych czasach PRL — uwagi wybrane na tle zakresu podmiotowego dopuszczalności arbitrażu (dawny art. 697 § 3 i 4 k.p.c.) - Budniak-Rogala, Aleksandra (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
This elaboration is an attempt to introduce an interpretation of former Art. 697 § 3 and 4 of the Civil Procedure Code regarding admissibility of concluding agreements for submitting disputes to an arbitration court by social economy entities. The analyzed provisions provided relevant limitations of the objective scope of admissibility of arbitration regarding said social economy entities – both in domestic and international transactions. It involved especially with the establishment of the State Economic Arbitral Institution. The solutions adopted by the legislator were undoubtedly the result of applying the principles of the socio-economic regime of the post-totalitarian Polish People’s Republic.
Keywords: scope of admissibility of arbitration; objective scope of admissibility of arbitration; ability of arbitration; social economy entities; arbitration in the era of the Polish People’s Republic